2016
DOI: 10.1139/cjz-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermal biology and depth distribution of largemouth bass (Micropterus salmoides) and northern pike (Esox lucius) in an urban harbour of the Laurentian Great Lakes

Abstract: Understanding how individuals are distributed in space and time, as well as how they interact with dynamic environmental conditions, represent fundamental knowledge gaps for many fish species. Using acoustic telemetry tags, we monitored the temperatures and depths used by northern pike (Esox lucius L., 1758) and largemouth bass (Micropterus salmoides (Lacepède, 1802)) in Toronto Harbour (Lake Ontario). Northern pike and largemouth bass had similar thermal experiences throughout the year, except during summer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Furthermore, electro‐anesthesia has been found to increase mortality in some fishes, particularly those with elongated bodies (i.e., Northern Pike; Peat et al. ). This concern, paired with the limited induction time, likely makes electro‐anesthesia inappropriate for gar surgeries, which require deeper anesthesia; however, this approach may still be valuable for applications where less complete induction is required (i.e., external tagging or to facilitate handling).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Furthermore, electro‐anesthesia has been found to increase mortality in some fishes, particularly those with elongated bodies (i.e., Northern Pike; Peat et al. ). This concern, paired with the limited induction time, likely makes electro‐anesthesia inappropriate for gar surgeries, which require deeper anesthesia; however, this approach may still be valuable for applications where less complete induction is required (i.e., external tagging or to facilitate handling).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…; Peat et al. ), but it is important to note that the presence of tilapia, a potential prey, had no meaningful influence on relative abundance of large Largemouth Bass, which are typically those most sought by anglers (Barnhart ; Noble ). Although we are not aware of other published research linking the presence of tilapia with Largemouth Bass abundance, our results are consistent with previous investigations that have indicated limited effects of interactions among these species (e.g., Gu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our results indicated that the abundance of large Largemouth Bass is primarily a function of abiotic factors including temperature and lake zone, a correlate of temperature. This result is not particularly surprising given the large body of literature describing the general effect of temperature on fish abundance, including Largemouth Bass (e.g., Hasler et al 2009;Peat et al 2016), but it is important to note that the presence of tilapia, a potential prey, had no meaningful influence on relative abundance of large Largemouth Bass, which are typically those most sought by anglers (Barnhart 1989;Noble 2002). Although we are not aware of other published research linking the presence of tilapia with Largemouth Bass abundance, our results are consistent with previous investigations that have indicated limited effects of interactions among these species (e.g., Gu et al 1996;Peterson et al 2006).…”
Section: Fall 2014mentioning
confidence: 92%
“…With few acoustic telemetry projects in the Great Lakes basin, little need existed during the early 2000s for the organization of a telemetry observation system. However, with advancements in telemetry technology combined with the research successes in the marine sector, use of acoustic telemetry in the Laurentian Great Lakes rapidly expanded during the next decade (e.g., Toronto Harbour project; Peat et al 2016;Rous et al 2017; sea lamprey Petromyzon marinus navigation, Meckley et al 2014Meckley et al , 2017, which provided the motivation to organize an observation system and eventually led to the creation of GLATOS.…”
Section: Introductionmentioning
confidence: 99%